CIRBP Knockdown Attenuates Tumourigenesis and Improves the Chemosensitivity of Pancreatic Cancer via the Downregulation of DYRK1B - Chen, Xiang; Xie, Hongyu; Wang, Xin; Zheng, Zhinan; Jin, Sanqing (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies worldwide with very limited treatment options. Cold-inducible RNA binding protein (CIRBP) plays promoting roles in several types of cancers, but its function remains unclear in PDAC. Here, we found that the expression of CIRBP was upregulated in PDAC tumour tissues and was significantly associated with poor prognosis. Knockdown of CIRBP in PANC-1 and SW1990 cells inhibited proliferation, migration and invasion in vitro and suppressed tumour growth in vivo. Moreover, CIRBP knockdown enhanced the antitumour effects of gemcitabine treatment in PANC-1 and SW1990 cells, whereas CIRBP overexpression exerted the opposite effects. Mechanistically, CIRBP promoted PDAC malignancy and chemoresistance via upregulation of dual-specificity tyrosine-Y-phosphorylation regulated kinase 1B (DYRK1B). Indeed, knockdown of CIRBP sensitized pancreatic tumours to gemcitabine treatment by diminishing DYRK1B expression and increasing the ratio of ERK/p38 activity. Our findings suggest that CIRBP overexpression facilitates PDAC progression and gemcitabine resistance by upregulating DYRK1B expression and inhibiting the ERK/p38 signalling pathway, highlighting CIRBP as a potential new therapeutic target for PDAC.